Nature resists in the city: protected areas in Buenos Aires city, citizen initiative and popular resistance (Papeles, 2022)
The aim of this paper is analyse how UPAs emerged in the Buenos Aires City from  citizens’ initiative, how different movements had to fight for their normative recognition and how we continue to struggle because there are permanent attacks from extractivist policies that seek to advance on them. We go deeper into the importance of UPAs and citizen actions and projects to create new ones, especially the Urban Protected Areas and the Neighbourhood Organizations Networks in CABA in the resistance against those who, without a social license, are trying to take away natural public green areas for the business of a few. We promote a paradigm shift in the way we inhabit this planet in defence of territories and biodiversity to share among all beings that inhabit the Pacha, and we encourage the implementation of this in cities as well. We mention some pending projects to expand the spaces of respect and expansion of biodiversity, such as ecological corridors and new protected areas. It is time to make necessary changes to avoid collapse. Law must respond to support the path towards Environmental and Climate Justice. Saving what we have left of Nature will help us to live an Urban Buen Vivir.
Keywords: protected areas; nature; city; wetlands; ecological corridors